2024
DOI: 10.5334/joc.351
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Motor Contributions to Auditory Statistical Learning

Sam Boeve,
Riikka Möttönen,
Eleonore H.M. Smalle

Abstract: Statistical learning is the ability to extract patterned information from continuous sensory signals. Recent evidence suggests that auditory-motor mechanisms play an important role in auditory statistical learning from speech signals. The question remains whether auditory-motor mechanisms support such learning generally or in a domain-specific manner. In Experiment 1, we tested the specificity of motor processes contributing to learning patterns from speech sequences. Participants either whispered or clapped t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Indeed, a follow-up study indicated that the developmental trajectories of visual and non-linguistic auditory SL are in fact similar when the auditory SL task used familiar sounds (e.g., a bird tweeting, a door opening) rather than syllables (Shufaniya & Arnon, 2018). Learning linguistic materials and non-linguistic materials were also found to be differentially affected by concurrent motor productionthe learning of linguistic sequences was hindered when participants had to whisper, whereas the learning of nonlinguistic sequences was not (Boeve et al, 2024). Together, these findings suggest that linguistic information may be processed and learned differently compared to non-linguistic information.…”
Section: Stimulus-sensitivitymentioning
confidence: 96%
“…Indeed, a follow-up study indicated that the developmental trajectories of visual and non-linguistic auditory SL are in fact similar when the auditory SL task used familiar sounds (e.g., a bird tweeting, a door opening) rather than syllables (Shufaniya & Arnon, 2018). Learning linguistic materials and non-linguistic materials were also found to be differentially affected by concurrent motor productionthe learning of linguistic sequences was hindered when participants had to whisper, whereas the learning of nonlinguistic sequences was not (Boeve et al, 2024). Together, these findings suggest that linguistic information may be processed and learned differently compared to non-linguistic information.…”
Section: Stimulus-sensitivitymentioning
confidence: 96%